Using Chemical Probes to Assess the Feasibility of Targeting SecA for Developing Antimicrobial Agents against Gram‐Negative Bacteria. (18th October 2016) - Jin, Jinshan; Hsieh, Ying‐Hsin; Cui, Jianmei; Damera, Krishna; Dai, Chaofeng; Chaudhary, Arpana S.; Zhang, Hao; Yang, Hsiuchin; Cao, Nannan; Jiang, Chun; Vaara, Martti; Wang, Binghe; et al.
Abstract: With the widespread emergence of drug resistance, there is an urgent need to search for new antimicrobials, especially those against Gram‐negative bacteria. Along this line, the identification of viable targets is a critical first step. The protein translocase SecA is commonly believed to be an excellent target for the development of broad‐spectrum antimicrobials. In recent years, we developed three structural classes of SecA inhibitors that have proven to be very effective against Gram‐positive bacteria. However, we have not achieved the same level of success against Gram‐negative bacteria, despite the potent inhibition of SecA in enzyme assays by the same inhibitors. In this study, we use representative inhibitors as chemical probes to gain an understanding as to why these inhibitors were not effective against Gram‐negative bacteria. The results validate our initial postulation that the major difference in effectiveness against Gram‐positive and Gram‐negative bacteria is in the additional permeability barrier posed by the outer membrane of Gram‐negative bacteria. We also found that the expression of efflux pumps, which are responsible for multidrug resistance (MDR), have no effect on the effectiveness of these SecA inhibitors. Identification of an inhibitor‐resistant mutant and complementation tests of the plasmids containing secA in a secAts mutant showed that a single secA ‐ azi‐9 mutation increased the resistance, providing genetic evidence that SecA is indeed the target of these inhibitors in bacteria. Such results strongly suggest SecA as an excellent target for developing effective antimicrobials against Gram‐negative bacteria with the intrinsic ability to overcome MDR. A key future research direction should be the optimization of membrane permeability. Abstract : Broad‐spectrum antimicrobials? SecA inhibitors are potent antimicrobials against Gram‐positive bacteria. Whether SecA is a valid target against Gram‐negative bacteria is an unanswered question. By probing the membrane permeability issue, we found that indeed inhibition of SecA leads to bacteriostatic and bactericidal effects against Gram‐negative bacteria. Such effects are not attenuated by the presence of efflux pumps, which are responsible for multidrug resistance. Therefore, SecA is an excellent target for developing broad‐spectrum antimicrobials against drug‐resistant bacteria.